Critical Heat Flux in Flow Boiling in Microchannels - Saha, Sujoy Kumar; Celata, Gian Piero (SpringerBriefs in Thermal Engineering and Applied Science,, 2015)
This Brief concerns the important problem of critical heat flux in flow boiling in microchannels. A companion edition in the SpringerBrief Subseries on Thermal Engineering and Applied Science to "Heat Transfer and Pressure Drop in Flow Boiling in Microchannels," by the same author team, this volume is idea for professionals, researchers, and graduate students concerned with electronic cooling.